Is Germany becoming the European pollution haven? - Kathrine von Graevenitz; Elisa Rottner; Philipp M. Richter (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2023)
Relative prices determine competitiveness of different locations. In this paper, we focus on the role of regulatory differences between Germany and other EU countries which affect the shadow price of carbon emissions. We calibrate a Melitz-type model, extended by firms' emissions and abatement decisions using data on aggregate output, trade and emissions. The parameter estimates are estimated from the German Manufacturing Census. The quantitative model allows us to recover a measure of how regulatory stringency evolved in the EU and Germany in terms of an implicit carbon price paid on emissions. This price reflects energy and carbon prices in addition to command-and-control measures and decreased from 2005 to 2019 in most sectors - both in Germany and other EU countries. The trend is more pronounced in Germany than in the rest of the EU. In counterfactual analyses, we show that this intra-EU difference has substantially increased German industrial emissions. Had the EU experienced the same decrease in implicit carbon prices as Germany, German emissions would have been substantially lower. Germany has increasingly become a pollution haven
Keywords: F18; H23; L60; Q56; 330; Carbon emissions; Climate Policy; Melitz model; Manufacturing